Utilização de dois intervalos de descanso entre pastoreios em pastagem natural com novilhas de corte na estação quente - Barbieri, Cezar Wancura (2013)
The aim of this study was to evaluate the performance and ingestive behavior of beef heifers grazing natural grassland managed under rotational grazing according to two rest periods in spring and summer. The treatments were two intervals between grazing 375 and 750 DD (degree days), based on thermal cumulative average for leaf expansion of native grasses belonging to two functional groups. The experimental design was randomized complete block design with two treatments and three replications. The experiment was conducted from November 2011 to April 2012. The test animals were Angus beef heifers, with an initial mean age of 12 months and initial weight 185.2 ± 17.4 kg. The ingestive behavior variables evaluated were grazing time, rumination and rest, and daily number and duration of meals, bite rate, number of stations visited per minute, number of steps between feeding stations, length of stay at the station. All variables of ingestive behavior were similar between treatments. However, grazing time and biting rate ranged between assessments. The different intervals between grazing on natural pasture did not influence the patterns of ingestive behavior of heifers. The variables of pasture mass of green leaf and stalk weight in different time periods evaluated the influence of grazing, ruminating and bite rate. Forage mass was higher in the 750 DD treatment, however, the mass of leaf blades were similar among treatments. The highest average daily gains and gains per area were observed in 375 DD treatment. In one evaluation period there was weight loss in animals of both treatments, that was attributed to a drought occurred and the lowest mass of leaf blades of the period. The average stocking density was similar between treatments. The treatment of lower defoliation interval presented greater individual gain.